Effectiveness of Akper Student Assistance to Mothers whose Children are Stunting - Tutik Setyowati; Yuni Astuti; Joni Siswanto (Journal of Midwifery Science: Basic and Applied Research, 2022)
Cases Stunting in children can be a predictor the low quality of a country's human resources. The state of stunting causes poor cognitive abilities, low productivity, and increased risk of disease resulting in long-term losses for the Indonesian economy. Nutrition problems, especially stunting in infants, can inhibit a child's development, with negative impacts that will last in the next life such as intellectual decline, susceptibility to non-communicable diseases, decreased productivity to cause poverty and the risk of giving birth to babies with low birth weight. Knowing the effectiveness of the assistance of Akper students to mothers who have children Stunting to Height / Length of Child Body. This research is a quasi-experimental quantitative research with a Pre and Post Test with Control Group Control Test design, where mothers who have stunting children are assisted by acper students by providing health education 6 properly taking medicine, immunization, breastfeeding Exclusive, MP-ASI, Nursing Mothers Nutrition and Benefits of Zynk and Fe. After mentoring, a re-evaluation of body length / height was then compared with the control group. Analysis of different tests using the Mann Whitney Test.The results of the statistical analysis of the treatment group accompanied by the student akper to the addition of the stunting length / height of the child obtained p = 0,000 (P0.05), the control group p = 0,000 (P0.05). Although equally significant changes occur in body length / height, if examined based on nutritional status (TB / Age) the control group only changes its status from very short to short. Adds because it is still involved in a period of growth and development but is not maximal compared to the assistance was carried out. This means that the child who is a control group is still in a stunting condition. However, the treatment group, from very short status to normal status, is free from stunting status. While Mann Whytney's different test in the treatment group and the control group results p = 0,000 (P0.05), meaning that the Akper student assistance for mothers whose children are stunting effectively increases the length / height of the child compared to the control group. The assistance of Akper students to mothers who have stunting children effectively increases the length / height of the child.